Knowledge audit process framework for inter-agencies collaboration - Ahmad, Nur Syufiza (2016)
Knowledge audit is a process to determine an organization’s knowledge asset. In the case of government inter-agencies special joint-operations, knowledge audit helps government agencies to better leverage knowledge for improving services and make better decisions based on what they know of their own knowledge. At present, there is no knowledge audit process specially catered for inter-agencies collaboration. This has hindered agencies from identifying their knowledge asset, and resulted in difficulties for agencies to collaborate efficiently. This research developed a Knowledge Audit Process for Inter-agencies (KAP-I) Framework. A Design Science Research methodology was carried out to ensure the rigor and relevance of the framework. Qualitative data were collected from a joint-operation of selected agencies involved in flood management as the case study. Data gathered from nineteen respondents of flood management agencies were analysed using knowledge sharing theory for inter-agencies. Theoretically, the technological, organizational and managerial, and political and policy perspectives were used to derive the knowledge audit elements. Using a deductive content analysis, twelve applicable knowledge audit elements for inter-agencies collaboration were discovered and later manifested in the framework. To ensure the efficacy and utility of the framework, formative and summative evaluations were conducted to iterate the artefact design. The framework was verified by practitioners who agreed with the logic and content, and they proposed suggestions for improvements. For verification, the framework was tested on the Independence Day Celebrations as a case study using structured walkthrough technique. Based on the findings, KAP-I Framework was formulated and it consists of three components: KAP-I Process, KAP-I Guide, and KAP-I Template that complement each other as a whole. The framework can be used to guide agencies through the inter-agencies knowledge audit process as it assists in the identification of special joint-operations related knowledge asset, as well as capture the experiential knowledge gained from the special joint-operations.